Design of Multiband Miniaturized Antenna using Metamaterial Concept for WLAN/WiMAX Application - Sofian Hamid (Universitas Al Azhar Indonesia, 2011)
Design of low cost multiband antenna is presented. The antenna works in WLAN/WMAX band and has a very compact dimension of 2 cm x 2 cm, making it suitable for handheld devices. This small dimension is achieved since the antenna is loaded with the metamateria element. To miniaturize the antenna dimension further, modification on the left side of ground-plane is introduced, which is inspired by the self complementary antenna concept. Resonance at lower frequency is given by the single cell metamaterial loading on 2.36 – 2.45 frequency; at the middle frequency is given by the thin slot on 3.26 – 3.49 frequency; and at higher frequency is given by the main radiator on 5.3 – 6 GHz frequency. The antenna has omnidirectional pattern and moderate directivity of 2-3 dBi on those frequencies.